Does transport affect the eating quality potential of beef from Limousin cows in France? - A case study - Nathalia da Silva Rodrigues Mendes; Renato Rodrigues Silva; Moïse Kombolo-Ngah; Pierre-Philippe Rivet; Jerôme Tondusson; Tatianne Ferreira de Oliveira; Sghaier Chriki; Marie-Pierre Ellies-Oury; Jean-François Hocquette (Veterinary and Animal Science)
We hypothesized that transportation might impact beef sensory quality, particularly as the distance between farms and the slaughterhouse increases. Specifically, we expected that pre-slaughter transport over longer distances would induce stress in the cattle, resulting in elevated ultimate pH and, consequently, reduced beef quality. Thus, this study aimed to specifically study the effects of transport in commercial conditions of Limousin cows from farms located in different areas of France to slaughter on ultimate pH (pHu) measured in the Longissimus thoracis muscle (LT), marbling (two major factors affecting eating quality) and the MSA Index (a global indicator of potential eating quality at the carcass level). Cattle were studied according to distance (<50 km; between 50 and 150 km; and between 150 and 250 km from the slaughterhouse) and according to transport time from the farm to the slaughterhouse (divided into short, moderate, and extended). We found that neither distance nor transport time significantly affected pHu of beef and the other studied parameters (cold carcass weight, meat color, MSA Marbling and MSA Index). Consequently, in our commercial conditions, we concluded that the effects of transport on beef carcasses and beef eating quality of Limousin cows are negligible.